Simulacija Bose-Einsteinovih kondenzatov - Cvetko, Tomaž (Matrika, 2019)
Bose-Einstein condensate is a state of matter of a dilute gas of bosons, where a macroscopic fraction of bosons occupies the lowest quantum state. This article discusses simulation of Bose-Einstein condensates and its relevance to experimental work with Bose-Einstein condensates. It starts with a description of laser cooling which enables condensation in experiments with cold atoms. An overview of the theoretical model for describing cold atom gas is then made and derivation of the Gross-Pitaevski equation briefly summarized. In the second part of the article an efficient algorithm based on spectral methods is presented as an efficient way of numerically solving nonlinear Schrödinger equation. An implementation of the algorithm is then applied to two specific one-dimensional examples and the results are compared to experiments.
Keywords: Bose-Einstein condensate; Bose-Einsteinov kondenzat; laser cooling; lasersko hlajenje atomov; statistical physics; statistična fizika